Adverse effects of the bite-raised condition in animal studies: A systematic review. (November 2019) - Piancino, Maria Grazia; Tortarolo, Alessandro; Polimeni, Antonella; Cannavale, Rosangela; Tonni, Ingrid; Deregibus, Andrea
Highlights: Raising the bite is a form of occlusal disharmony. In animal models, it is associated with three main adverse effects. It is associated with alterations along the hypothalamic-pituitary-adrenal axis. It is associated with a reduction of hippocampal neurons and increased astroglia. It is associated with altered masticatory muscle activation during chewing. Abstract: Objective: To provide a systematic review of the effects of the bite-raised condition in animal models, a widespread technique in modern orthodontics. Design: A systematic review of the literature was conducted. Original articles were searched through Pubmed, Cochrane Central database and Embase until December 2018. Results: 242 articles were identified through database searching. After removing the duplicates, 198 articles were screened by reviewing the abstracts. 27 full text articles were assessed for eligibility and, after 7 exclusions, 20 articles were included in the review process. Studies selected by the review process concerned animal models. Histological, molecular, biochemical and electromyographical studies were evaluated. The results, with a high level of agreement in different animals, showed that the bite-raised condition is a source of stress, inducing increased plasma corticosterone, urinary cortisol and HPA axis alterations; it predisposes the organism to react to subsequent stressful stimulation with a significantly greater incretion of glucocorticoids, thus inducing hypersensitivity to novel forms of stress; it affects the structure of the hippocampus, reducing the number of neurons, increasing the number of glial cells and worsening memory and spatial orientation; it alters the electromyographical activity of masticatory muscles. Conclusions: The results of research conducted on animal models do not necessarily apply directly to human beings. More clinical research, with special attention to adolescent patients, is necessary to clarify whether, in humans, the bite-raised condition is accompanied by adverse effects comparable to those observed in animals.